Effects of substituting rice straw with different levels of Leucaena leucocephala (Lam.) de wit and Manihot esculenta crantz leaves on rumen fermentation characteristics and microbial population in goats - Harun, Nur Liyana Akmal (2015)
The leaves of L. leucocephala and M. esculenta are among good source of protein and its use in animal feed would further increase the nutritive value of poor quality feed. Generally, the presence of the anti-nutritive factors contained in both of the forages limit their usefulness as animal feed, but not in ruminant. Ruminant have a dynamic and complex rumen ecology that may have the ability to degrade the anti-nutritive factors contained in the L. leucocephala and M. esculenta leaves. Most of the previous studies are focused on the effect of L. leucocephala and M. esculenta leaves on performances and health of the animal. Therefore, current study was conducted to evaluate the effect of substitution rice straw with different level of L. leucocephala and M. esculenta leaves on rumen fermentation characteristics and rumen microbial population in goats. Seven treatment groups; T1: concentrates (C)/rice straw (RS) (40:60) (Control); T2: C/RS/leucaena leaves (40:45:15); T3:C/RS/leucaena leaves (40:30:30); T4: C/RS/leucaena leaves (40:15:45); T5:C/RS/cassava leaves (40:45:15); T6:C/RS/cassava leaves (40:30:30) and T7: C/RS/cassava leaves (40:15:45) were used in this experiment. An in-vitro study was carried out to evaluate the effect of substitution of rice straw with different level of L. leucocephala and M. esculenta leaves diet on rumen gas production and fermentation characteristics. In the in-vitro study, the production of propionate and IVDMD were significantly affected with the treatment diets (P<0.05). Propionate production was significantly increased meanwhile the percentages of IVDMD was decreased significantly with T2 showed the highest value in the propionate production and the lowest value of IVDMD. Similar observation were found among treatment diets in rumen pH, rumen ammonia, acetate,butyrate, total VFA production and total gas production of the in-vitro study. In the invivo study, 21 local Boer goats were randomly divided into seven diets and were placed in metabolic cages individually for a period of 7 days as an adjustment period followed by an administration diet period for 10 days. Urine samples were taken daily for 5 days period for urinary purine derivatives analysis and rumen samples were taken at day 10 for rumen fermentation characteristics and rumen microbial population quantification analysis. Result shown that propionate (P<0.05), butyrate (P<0.01), A to P ratio (P<0.05), total VFA production (P<0.01) were affected significantly among the treatment diets. The highest value of acetate, A to P ratio and total VFA were found in T2 with the lowest value of propionate. Supplementation of L. leucocephala and M.esculenta leaves diets demonstrated significant increase (P<0.01) in the production of rumen ammonia. There were no differences shown in the rumen pH and production of acetate. Urinary allantoin (P<0.05), xanthine (P<0.05), total PD (P<0.05), microbial purine absorbed (P<0.01) and microbial N supply (P<0.01) were affected significantly with T2 and T6 showed the highest value among the treatment diets whereas production of uric acid, hypoxanthine showed similar observation. In the microbial population study, the supplementation of L. leucocephala or M. esculenta leaves in the diet had increased the population of total protozoa and R. flavefacien significantly (P<0.05) with T4 and T7 showed the highest value, respectively. Meanwhile, the populations of R. albus, and F. succinogenes were significantly reduced (P<0.05) with T3 and T7 showed the lowest value, respectively. In conclusion, T2 (25% of L.leucocephala leaves) and T6 (50% of M. esculenta leaves) supplementation diet are suitable diet for goat consumption due to improvement in the VFA production, urinary purine derivative productions, microbial purine absorbed and microbial N supply with moderate amount rumen microbial population.